2017
DOI: 10.3892/etm.2017.5388
|View full text |Cite
|
Sign up to set email alerts
|

Application of novel targeting nanoparticles contrast agent combined with contrast‑enhanced computed tomography during screening for early‑phase gastric carcinoma

Abstract: Gastric cancer is one of the most common human tumors worldwide. The biggest bottleneck is a lack of advanced and sensitive protocols for the diagnosis of patients with early-stage gastric cancer. Therefore, more sensitive methods of diagnosing gastric cancer are urgently required to improve survival rates. In this clinical study, contrast-enhanced computed tomography (CECT) with targeting nanoparticles contrast agent (CECT-TNCA) was used to diagnose early-stage gastric cancer. The specific-targeted tyrosine k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Here, we found that RET was significantly upregulated in GC tissues in relation to normal gastric mucosa, supporting the similar findings of Zhang et al, and their conclusion that RET overexpression may be one of the molecular changes driving gastric carcinogenesis 34 . This is additionally underpinned by the fact that the new diagnostic method developed by Zhang et al, based on contrast-enhanced computed tomography (CECT) combined with liposome-encapsulated targeted contrast agents containing tyrosine kinase inhibitors of GC, including RET, allowed for the effective diagnosis of patients in the early stage of gastric cancer 53 . To our knowledge, the cited study of Zhang et al is the only one existing in the scientific literature which assessed by IHC the expression level of RET protein in the series of GC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that RET was significantly upregulated in GC tissues in relation to normal gastric mucosa, supporting the similar findings of Zhang et al, and their conclusion that RET overexpression may be one of the molecular changes driving gastric carcinogenesis 34 . This is additionally underpinned by the fact that the new diagnostic method developed by Zhang et al, based on contrast-enhanced computed tomography (CECT) combined with liposome-encapsulated targeted contrast agents containing tyrosine kinase inhibitors of GC, including RET, allowed for the effective diagnosis of patients in the early stage of gastric cancer 53 . To our knowledge, the cited study of Zhang et al is the only one existing in the scientific literature which assessed by IHC the expression level of RET protein in the series of GC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing various medical topics using liposomal delivery systems for imaging and therapy, oncology is the area with the biggest collection of data referring to its broad application. Liposome-nanoparticle hybrids that include metallic components such as: gold nanoparticles [75,81] or gadolinium nanoparticles (GdNPs) [63,82,83], and ultrasuperand superparamagnetic iron oxide nanoparticles (SPIONs)-called magnetoliposomes (MLs) [60,84,85]-can serve in the visualization of the cancer tissues using CT and MRI. Liposome-based CAs incorporating gadolinium were the first introduced nanostructure that has been widely used in various systems [86][87][88].…”
Section: Medical Imagingmentioning
confidence: 99%
“…NVs can be conjugated with QDs to function as vehicles to transport specific therapeutic cargo (eg aptamer) to target GI premalignant lesions directly 19,56. A vesicle composite probe is constructed in multiple steps to carry a specific aptamer for direct detection of the lesion (Figure 2).…”
Section: Combined Targeting Of Nvs and Hif Against Gi Premalignant Lementioning
confidence: 99%
“…Localized surface plasmon resonance biosensors with self-assembled gold nanoislands (SAM-AuNIs) has been demonstrated to be another direct method for direct target detection and this method may be able to distinguish exosomes from different sources 57. QD-conjugated NVs encapsulated with NPs can also be used as various imaging contrast agents, in combination with computer tomography and other imaging tools, as an indirect method to identify GI lesions 1921Figure 2Using QD-conjugated NVs to directly detect GI premalignant lesions.…”
Section: Combined Targeting Of Nvs and Hif Against Gi Premalignant Lementioning
confidence: 99%